A review of the Sustainability and Parametric Design Approach of Complex Tall Buildings at an Early Design Stage - Al-Masoodi, A.H.H. (Institute of Electrical and Electronics Engineers Inc., 2021)
The vertical city building is gaining popularity because of rapid urban population growth, economic expansion, limited urban space, technological development and increasing demand for residential and commercial buildings. Tall buildings with irregular forms are designed and built today with the help of computational technologies. This paper reviews two parts. In the first part, it collects and discusses a wide range of fragmented criticisms and concerns that may be associated with tall building lifestyles around three pillars of sustainable development, such as social, environmental, and economic; in order to examine gaps and guide the technological direction of tall building design in the future. Secondly, this paper describes a unique design technique based on a parametric approach by utilizing computational tool components. Finally, a framework is proposed for achieving an optimum design by using parametric software in order to satisfy environmental criteria as well as structural efficiency of tall buildings at an early stage of the project. Â© 2021 IEEE.